Research on a stable clustering algorithm based on the optimal connectivity power for wireless sensor networks - LI Fang-min1; LIU Xin-hua1; KUANG Hai-lan1; FANG Yi-lin1 (Tongxin xuebao)
In realistic environment, the actual layout of nodes is easy to make network separated and nodes are always densely deployed in hot spots like the site of an accident or disaster where the competition intense was very high.A stable clustering algorithm based on the optimal connectivity power for wireless sensor networks was proposed.The algorithm makes use of the alterable power control technology to raise the channel utilization ratio and network throughput based on the optimal number of neighbors, and realizes the stable connectivity and clustering of network.The algorithm simplifies the topology of network so that prolong the network lifetime at the best.The simulation results show that the algorithm maintains the connectivity and stability of network effectively, and has good auto-adapted ability to environment and obvious effects in the promotion of whole performance of network.